Evaluación de la interacción de niveles de fertilizantes y mezclas de herbicidas en el cultivo de arroz (Oryza sativa L.) - Aragundi Torres, Vicente Andrés (2016)
VIII. SUMMARY This research was conducted in the grounds of the farm "San Pablo" of the Technical University of Babahoyo, located at Km 7.5 of Babahoyo satellite -. Montalvo, with geographic coordinates 79ᵒ 32 'west longitude and 49 01ᵒ' of South longitude and altitude of 8 meters. The area has a tropical climate with average temperature of 24,2ᵒ C, annual rainfall of 1818.6 mm, relative humidity of 86.3% and 834.9 hours annual heliophany. The floor is flat topography, clay loam texture and regulate drainage. rice variety INIAP 15, which was obtained at the Autonomous National Agricultural Research Institute was used. In the development of research-based treatments Nitrogen (120 kg / ha) + Phosphorus P2O5 (20 kg / ha) + Potassium K2O (20 kg / ha) were used; Nitrogen (140 kg / ha) + Phosphorus P2O5 (30 kg / ha) + Potassium K2O (40 kg / ha); Nitrogen (160 kg / ha) + Phosphorus P2O5 (40 kg / ha) + Potassium K2O (60 kg / ha); Nitrogen (180 kg / ha) + Phosphorus P2O5 (50 kg / ha) + Potassium K2O (80 kg / ha) and subtratamientos based clomazone + pyrazosulfuron ethyl (1.0 L + 0.35 kg); Metsulfuron methyl + propanil (15 g + 3 L) and Pyribenzoxim + 2,4 D amine (1.0 L + 0.7 L). In this research design it was used divided plots, whose treatments were constituted by fertilizer levels, subtreatments by the mixtures of herbicides and three repetitions. For comparison of averages the Tukey test at 5% significance was used. farming required, such as soil testing, land preparation, planting, watering, fertilizing, weed control, plant protection, harvesting took place. To estimate the effects of treatments and data subtratamientos toxicity index at 7 and 14 days were evaluated height after application of herbicides, weed control at 15 and 30 days after application of the herbicide, plant harvest, number of tillers / m2, panicle number, days to flowering, physiological maturity, panicle length, grains per spike, 1000 grain weight, grain yield and economic analysis. By the above results it was concluded that the interaction of levels of fertilizer and herbicide mixtures had positive effects on the production of rice (Oryza sativa L.) in the area of Babahoyo; after 7 days in culture toxicity it was undamaged after 14 days showed little damage; the best weed control was presented with mixtures Pyribenzoxim +2.4 D amine (1.0 L + 0.7 L) at 15 and 30 days after application of the products; agronomic traits such as plant height, tillers and panicles / m2, panicle length and grains per spike were influenced in their averages with the application of nitrogen (160 kg / ha) + Phosphorus P2O5 (40 kg / ha) + Potassium K2O (60 kg / ha); in days to flowering and physiological maturity all treatments and subtratamientos responded equally by the variety used Iniap 15; the highest 1000 grain weight and performance are introduced in the application of nitrogen (160 kg / ha) + Phosphorus P2O5 (40 kg / ha) + Potassium K2O (60 kg / ha) and mixtures of herbicides applied in the three subtratamientos and the highest net profit was realized as applying nitrogen fertilizer (160 kg / ha) + Phosphorus P2O5 (40 kg / ha) + Potassium K2O (60 kg / ha) complementary mixtures based herbicides clomazone + pyrazosulfuron ethyl (1.0 L + 0.35 kg) to $ 662.02 / ha.